Angry faces are more resistant to forgetting than are happy faces: directed forgetting effects on the identity of emotional faces. Issue 7 (3rd October 2017) - Tay, Peter K. C.; Yang, Hwajin
ABSTRACT: Using the item-method directed forgetting paradigm (i.e. intentionally forgetting specified information), we examined directed forgetting of facial identity as a function of facial expression and the sex of the expresser and perceiver. Participants were presented with happy and angry male and female faces cued for either forgetting or remembering, and were then asked to recognise previously studied faces from among a series of neutral faces. For each recognised test face, participants also recalled the face's previously displayed emotional expression. We found that angry faces were more resistant to forgetting than were happy faces. Furthermore, angry expressions on male faces and happy expressions on female faces were recognised and recalled better than vice versa. Signal detection analyses revealed that male faces gave rise to a greater sensitivity than female faces did, and male participants, but not female participants, showed greater sensitivity to male faces than to female faces. Several theoretical implications are discussed.